Adenomatous polyposis coli gene large deletions in Iranian patients with familial adenomatous polyposis - Kishani Farahani, R; Montazer Haghighi, M; Asadzadeh Aghdaei, H; Keshavarzi, F; Taleghani, MY; Goodarzi, F; Nazemalhosseini-Mojarad, E; Zali, MR (Indian journal of cancer, 2014)
Context: Familial adenomatous polyposis (FAP) is one type of hereditary colon cancer with a large number of precancerous polyps that initiation to growth in childhood and adolescent. Mutation in adenomatous polyposis coli (APC) gene is the cause of FAP. Aims: The aim of the current study was to standardize multiplex ligation probe amplification (MLPA) method in screening of APC large deletions for the first time in Iranian patients with FAP. Subjects and Methods: Deoxyribonucleic acid was extracted from 34 FAP patients by saluting out method. All patients were screened for APC large deletions whit MLPA and for the positive results, respective region was investigated by polymerase chain reaction sequencing. All genetic alterations were doubled checked in two separated rounds of MLPA. Results: The detection rate of large fragment deletions in APC was 5.8% (2/34). Both of the Iranian patients had deletion in the middle and the end of exon 15, however, comparing of clinical features between patient with the large deletion and patients without deletion did not show any significant difference in each variable including, age at diagnosis, signs of disease and poly type. Conclusions: It seems that exon 15 of APC gene is probably the hotspot region in Iranian FAP patients. Association of genotype/phenotype is well known in FAP patients, but in this study statistical analyses did not show a significant difference in each considerable factor between patients with and without large deletions. It seems better to consider MLPA as an initial step to screening APC mutations.